Separating Leadership from Pay. Issue 1 (6th April 2017) - Hostettler, Stephan; Lambin, Raphaël
Abstract : Performance management and incentive systems can play an important role in shaping a company's culture and promoting internal collaboration. Yet, in an uncertain and rapidly evolving world that rewards organizations for agility, performance management systems based on a single individual overall rating are being viewed with growing skepticism; and the once common practice of tying pay directly to such ratings is being reconsidered—and in many cases abandoned. But when carrying out this process of "separating leadership from pay, " companies must commit to providing employees with extensive ongoing feedback, as well as significant opportunities for development and growth that are not linked directly to financial rewards. In place of traditional bonus schemes whose payoffs are tied to individual performance measures, the authors also recommend the use of company‐wide bonus plans—similar in spirit to the General Motors plan described earlier in this issue—that reflect a philosophy of "sharing success" that aims to encourage and reinforce a culture of collaboration and agility. But for compensation plans built around sharing success to be effective, careful attention should be given to the "quality" of the results achieved. This can be accomplished by supplementing the use of Key Performance Indicators—such as, for example, economic profit—with the use of so‐called "boundary" KPIs—such as the percentage of satisfied clients—for which a minimum threshold must be met.